SEKS BEBAS DAN KEHAMILAN YANG TIDAK DIINGINKAN - Elly Susilawati (Poltekkes Kemenkes Riau, 2026)
During adolescence, individuals generally exhibit a strong curiosity about their surroundings. This encourages them to explore, seek new experiences, and try new things (Azinar, 2013). At this stage, adolescents generally exhibit a high level of curiosity, a passion for trying new things, and a tendency to make decisions without carefully considering the risks. Therefore, various problems can arise during adolescence, including those related to romantic relationships and premarital sexual behavior (Handayani & Ratnasari, 2023). Premarital sexual behavior involves physical contact with the opposite sex and can develop into an intimate relationship. Sexual behavior can be divided into risky and non-risky sexual behavior (Maya Icha Gayatri, 2020). Unintended pregnancy is one of the common consequences of premarital sexual relations among adolescent girls. This condition is generally related to puberty, a developmental phase that occurs during adolescence (Fauziah & Subiyatin, 2022). The purpose of this community service activity was to increase adolescent knowledge about promiscuity and unwanted pregnancy. It took place on January 12, 2026, in Classroom 1 of the Nursing Students of the Applied Nursing Undergraduate Program at the Riau Ministry of Health Polytechnic. The community service activity began with education about promiscuity and unwanted pregnancy, followed by a discussion and Q&A session.